AAR 4200 architectural design 8 - project brief for high rise building design 2009-10 : vertical hospital - Mohd Nawawi, Norwina; Soomro, Ali Raza; Ismail, zamri (International Islamic University Malaysia (IIUM), 2009)
This a project brief for an academic architectural highrise project of the semester for bachelor of architecture programme that provide emphasis on highrise structure,potential repeat space planning, exposure of building services characterise in high rise structues and the need for safety, security and maintenance. For this semester, a hospital is selected as a building typology. Group work is envisaged at the early stages of the project where a live project was acquired from industry. Individual proposal ensued upon individual design brief is acertained. Students are not expected to design the whole hospital as a vertical hospital and were assigned 3 areas that govern the entrance at the footend, the podium as Outpatient and typical diagnostic space and ward on the tower. The whole process was tedious as students need constant guide on the project. Workshops were employed to provide the necessary detail hands on input. The outcome at the end of the semester were very good as students showed good understanding of their project. Most of these graduates were eventually employed to do hospitals in their respective firms even before they graduate!